THE EFFECT OF SQ3R METHOD ON THE STUDENTS’ ABILITY IN READING COMPREHENSION - Annisa Hutasuhut; Elia Masa Gintings (Universitas Negeri Medan, 2015)
The aim of this study is to discover the effect of applying SQ3R method in reading comprehension. Experimental research design is used as the research method. This research took place at MTS AMIN DARUSSALAM MEDAN. There were 2 classes chosen as the sample with 32 students in each class. The classes were divided into two groups namely experimental and control group. The experimental group taught by using SQ3R method and the control group was taught by using conventional method. The instrument used to collect the data was a set of multiple choice tests, which divided as pre test and post test. The result of the research was analyzed by using t-test formula. The result showed that t-test was higher than t-table ( 3,93> 2,00 ) at the level of significant 0,05 with degree of freedom (df) 60. It means that hypothesis alternative (Ha) is accepted which shows that SQ3R method significantly improves the student’s reading comprehension.